A method for estimating the remaining life of power transformers considering loading, hotspot temperature, and oil assessment - Rohmanita Duanaputri; Rizky Anjani; Rahman Azis Prasojo; Muhammad Fahmi Hakim; Dhimas Dhesah Kharisma (Center for Science and Technology, IAIN Surakarta, 2024)
Power transformers face significant aging issues, which threatens their reliability and service life. This research aims to develop an accurate method for predicting the remaining lifespan of transformers. Current studies highlight the inadequacy of existing approaches in determining transformer lifespan, which is affecred by the degradation of paper insulation through furan compounds and hotspot temperatures. This method adheres to the CIGRE D1 738 (2018) standard, which converts furan concentration into Degree of Polymerization (DPest) as an indicator of paper insulation condition. The methodology involves analyzing oil test data and operational temperature to estimate the remaining life of the transformer. This research not only aims to improve the accuracy of paper insulation assessments but also integrates sustainability principles. The goal is to optimize the use of existing transformers, reduce premature replacements, and conserve material and energy resources. By minimizing unexpected failures, this research contributes to reducing industrial waste and environmental impact. Furthermore, this approach aligns with practices that support economic and social sustainability. Extending the lifespan of critical devices can lower maintenance costs while ensuring a reliable and sustainable energy supply. The proposed method provides a comprehensive framework for predicting transformers longevity.